2015
DOI: 10.3389/fnhum.2015.00052
|View full text |Cite|
|
Sign up to set email alerts
|

A comparison of two sleep spindle detection methods based on all night averages: individually adjusted vs. fixed frequencies

Abstract: Sleep spindles are frequently studied for their relationship with state and trait cognitive variables, and they are thought to play an important role in sleep-related memory consolidation. Due to their frequent occurrence in NREM sleep, the detection of sleep spindles is only feasible using automatic algorithms, of which a large number is available. We compared subject averages of the spindle parameters computed by a fixed frequency (FixF) (11–13 Hz for slow spindles, 13–15 Hz for fast spindles) automatic dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 50 publications
(83 reference statements)
9
88
0
Order By: Relevance
“…We detected and subtyped spindles using fixed‐frequency cut‐offs, which is an area of inconsistencies as it has been suggested that there are pronounced inter‐subject differences in the frequency profiles of fast and slow spindles (Bodizs, Kormendi, Rigo, & Lazar, ; Ujma et al., ). Despite inter‐subject variation in oscillation frequency and frequency boundary for subtyping spindles, we chose in this study to detect spindles using an automatic detector that is rather simple and has been used and validated previously (Christensen et al., ; Latreille et al., ; Martin et al., ; Schabus et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…We detected and subtyped spindles using fixed‐frequency cut‐offs, which is an area of inconsistencies as it has been suggested that there are pronounced inter‐subject differences in the frequency profiles of fast and slow spindles (Bodizs, Kormendi, Rigo, & Lazar, ; Ujma et al., ). Despite inter‐subject variation in oscillation frequency and frequency boundary for subtyping spindles, we chose in this study to detect spindles using an automatic detector that is rather simple and has been used and validated previously (Christensen et al., ; Latreille et al., ; Martin et al., ; Schabus et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep spindles were detected with the Individual Adjustment Method(Bodizs, Kormendi, Rigo, & Lazar, 2009;Ujma et al, 2015), which uses individual frequency bands and amplitude criteria for sleep spindle detection. Sleep stages were scored on the basis of the EEG according to standard criteria and artefacts were manually removed using 4-s epochs.…”
mentioning
confidence: 99%
“…Sleep stages were scored on the basis of the EEG according to standard criteria and artefacts were manually removed using 4-s epochs. Sleep spindles were detected with the Individual Adjustment Method(Bodizs, Kormendi, Rigo, & Lazar, 2009;Ujma et al, 2015), which uses individual frequency bands and amplitude criteria for sleep spindle detection. We performed spectral analysis for all chan-nels (fast Fourier transformation, Hanning window, 20-s epochs) with 0.25 Hz frequency bins between 1 and 48 Hz.…”
mentioning
confidence: 99%
“…Based on individually identified peaks in the NREM sleep power spectrum at topographical locations where slow and fast spindles are expected (cf. Supplementary Figure 2), individually adjusted spindle frequency ranges can be definedeven if they might not match conventionally prescribed bands exactly (Adamczyk et al, 2015;Bódizs et al, 2009;Cox et al, 2017;Doppelmayr et al, 1998;Grandy et al, 2013;Klimesch, 1999;Ujma et al, 2015). Comparisons between spindle detection algorithms that use commonly predefined frequency ranges and those that adjust their frequency range definitions within individuals, provide a strikingly poor agreement with conventional (fixed frequency) algorithms.…”
Section: Inter-individual (Age) Variation In Fast and Slow Spindle Frmentioning
confidence: 99%
“…Standard criteria to describe these age-related alterations in sleep physiology are only rarely tested and validated within heterogeneous samples that include older adults (but see, e.g., Ujma et al, 2015Ujma et al, , 2019Warby et al, 2014). Therefore, in the following, we aim to demonstrate the possible benefits and limitations of applying established indicators of sleep physiology in the context of aging 4 research.…”
Section: Introductionmentioning
confidence: 99%